A Cross-sectional Study of Musculoskeletal Symptoms and Risk Factors in Cambodian Fruit Farm Workers in Eastern Region, Thailand - Anamai Thetkathuek; Parvena Meepradit; Teerayut Sa-ngiamsak (Elsevier, 2018)
Background: Work-related musculoskeletal disorders are accumulative disorders that are most frequently found in agricultural farmers. The purpose of this study was to investigate factors that affect symptoms resulting from work-related musculoskeletal disorders among Cambodian farm workers working in fruit plantations in the eastern region of Thailand. Methods: The Nordic Musculoskeletal Questionnaire, Rapid Upper Limb Assessment, and Hazard Zone Jobs Checklist techniques were used to interview 861 farmers who participated in the study. Results: The data showed that men who had been working for >10 years were more at risk of neck pain than those working for <1 year with adjusted odds ratio (aOR) 1.66, 95% confidence interval (CI) (1.90, 14.5). Among women those who had been working for >10 years experienced lower back pain with aOR 8.13, 95% CI (1.04, 63.74), compared with those who had been working for <1 year. Men whose tasks required raising the arms above shoulder height had a risk factor contributing to neck pain of aOR 1.68, 95% CI (1.08, 2.61) when compared with those who did not work with this posture, and women had aOR 1.82, 95% CI (1.07, 3.12) when compared with those who did not work with this posture. Conclusion: Based on the results of this study, it is recommended that work-related health conditions are monitored in migrant plantation workers to reduce the risks of musculoskeletal disorders. Keywords: agriculture, Cambodian workers, eastern Thailand, migrant, musculoskeletal disorder